Unveiling ancestral land: Alkebu-lan practices of human habitation Ebandleni - Mahlangu, Kenneth Mxolisi (School of Architecture, Planning and Geomatics, 2024)
Our cities can be perceived as palimpsests of sequential historic events that contributed to what the cities have become in the present age. Each event or occurrence produced and brought forth the intangible spirit of the time and place relatively, the aura, which can manifest through the people, culture, identity, or environment. Due to colonization, certain fundamental historical links and clues to who we are at our essence are hidden and distorted to be lost in history, along with them, the aura they possess is subdued. Consequently, what makes up the aura becomes extinct. The languages (mother tongue), the culture, the ways of creating artefacts, the art, the belief systems, the understanding of self and the environment (physically and spiritually), and at the end of it all, yourself. This dissertation situates itself in the context of the city of Tshwane, as the ancestral land. The settling of the AmaNdebele people pre-colonization is the root at the base of the city's palimpsest that seeks to be unveiled, celebrated, envisioned, and progressed in thought and making in what is an African city in the present day. The historic events that took place on the land saw unfortunate and unprecedented struggles and deterred the progress of a people for decades. Keywords: African, space, city-centre, culture, decolonisation, urbanism, social architecture, spirituality, reclaimation